2014
DOI: 10.1001/jamasurg.2013.3643
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dissemination of Circulating Tumor Cells With No-Touch Isolation Surgical Technique in Patients With Pancreatic Cancer

Abstract: Circulating tumor cells (CTCs) disseminate from the primary tumor and travel through the bloodstream and lymphatic system. The detection of and/or increase in the number of CTCs during a patient’s clinical course may be a harbinger of forthcoming overt metastasis. We aimed to examine the impact of 2 different surgical techniques, standard (ST) pancreaticoduodenectomy (PD) and no-touch isolation (NT) PD, on tumor behavior and outcome in patients with pancreatic cancer by using CTCs as biomarkers. In this pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 32 publications
1
54
0
1
Order By: Relevance
“…One explanation for why the OS is not different between the NACT + RH and CRT groups could be that the tumor size is larger in FIGO stage IIB cervical cancer when compared with early-stage tumors, and therefore, there is an increased opportunity for the stage IIB tumors to be disseminated during or after surgery. 26 When considering the long-term prognosis of cervical cancer, especially in young patients, there is a special emphasis on how to improve the quality of life of cancer survivors without increasing the risk of tumor recurrence., Treatment-related complications in cancer therapy are inevitable; radiotherapy and CCRT both result in menopausal symptoms, sexual dysfunction, and irreversible damage to the pelvic organs. The adverse effects associated with these treatments lead to a poorer quality of life for survivors.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for why the OS is not different between the NACT + RH and CRT groups could be that the tumor size is larger in FIGO stage IIB cervical cancer when compared with early-stage tumors, and therefore, there is an increased opportunity for the stage IIB tumors to be disseminated during or after surgery. 26 When considering the long-term prognosis of cervical cancer, especially in young patients, there is a special emphasis on how to improve the quality of life of cancer survivors without increasing the risk of tumor recurrence., Treatment-related complications in cancer therapy are inevitable; radiotherapy and CCRT both result in menopausal symptoms, sexual dysfunction, and irreversible damage to the pelvic organs. The adverse effects associated with these treatments lead to a poorer quality of life for survivors.…”
Section: Discussionmentioning
confidence: 99%
“…. Seventeen studies were suitable for inclusion, giving a total of 1472 patients for the meta‐analysis, of which 771 underwent an artery‐first pancreatoduodenectomy and 701 a standard pancreatoduodenectomy ( Table ). The mean(s.d.)…”
Section: Resultsmentioning
confidence: 99%
“…The posterior and anterior approaches were the most commonly described artery‐first approaches. Others included the mesenteric (inferior infracolic), medial uncinate, left posterior and superior approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gall et al has employed a no-touch isolation technique for pancreaticoduodenectomy. Although this new technique significantly reduced CTCs postoperatively compared to the standard technique, no survival benefits were observed [38]. Bissolati et al has found that the incidence of liver metastasis was significantly lower in patients without detectable CTCs compared to patients with CTCs (8% vs. 53%, p=0.038) [39].…”
Section: Prognostic Values Of Pancreatic Ctcsmentioning
confidence: 94%